Victimological Study of Children as Victims of Acts Criminal Trafficking in People - Lubis, Hawani; Halawa, Firman; Sahlepi, Muhammad Arif (PT FORMOSA CENDEKIA GLOBAL, 2024)
Victimology is the study of victimization, which includes analysis of the causes and effects of victimization in a social context. This term comes from Latin victima (victim) and logos(knowledge). Victimology seeks to understand various aspects of victimization and the criminal process, as well as the factors that lead to someone becoming a victim and their impact on the individual and society. In Indonesia, child protection is regulated in several laws which aim to ensure the welfare and rights of children. Based on Law Number 23 of 2002 concerning Child Protection, every child has the right to practice religion, think and express themselves according to their age and level of intelligence under the guidance of their parents. This law also emphasizes children's rights to know and be cared for by their biological parents. Meanwhile, Law Number 35 of 2014 defines children as individuals who are not yet 18 years old, including those who are still in the womb. This law emphasizes the need to protect children to ensure they can live, grow and develop optimally, and are protected from violence and discrimination. Protection of children is also regulated in Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. This law aims to tackle and criminalize all forms of human trafficking that involve exploitation. The definition of human trafficking according to this law includes acts such as recruiting, transporting, harboring, and receiving a person with threats or violence, fraud, forgery, or abuse of power, both within the country and between countries, with the aim of exploitation. With these various regulations, it is hoped that children can be protected from various forms of violence, exploitation and rights violations that they may experience